The Difference of Surface Roughness of Heat Cured Acrylic Resin After Brushing with 30% and 60% Lemongrass Extract in Pasta - Clarissa Valerie Wardojo; Paulus Budi Teguh; Linda Rochyani (Denta Journal Kedokteran Gigi, 2019)
Background: Tooth loss can be replaced by the use of dentures. Cleaning of dentures by brushing using toothpaste can cause surface roughness because of abrasive materials. The use of toothpaste can be replaced with paste of extract Cymbopogon citratus because it has antibacterial and antifungal effects. Purpose: to determine the effect of brushing using paste of extract Cymbopogon citratus on the surface roughness of heat cured acrylic resin. Methods: Sample were heat cured acrylic resin (62.5 x 10 x 2.5) mm, divided into 4 groups consist of negative control group was brushed with basic paste, positive control group was brushed with herb paste, and two groups were brushed with paste of Cymbopogon citratus extract with 30% and 60% concentrations. Brushing was done for 3 minutes with 60 brushing times and then measured with surface roughness tester. The data was processed by ANOVA test. Result: The average surface roughness in K-, K+, P1, and P2 were 0,1217, 0,3433, 0,1633, and 0,27 μm. There was significant difference between negative control group and positive control group; negative control group with P1 and P2 group; positive control group with P1 and P2 group; P1 group with P2 group (P <0.05). Conclusion: The paste of Cymbopogon citratus extract concentration of 30% was effectively used because the level of surface roughness below the maximum limit of recommended surface roughness of dentistry material which is 0,2 μm. The 60% concentration paste of Cymbopogon citratus extract was less effective because the level of surface roughness above the maximum limit of surface roughness is recommended.